Chemometric Analysis of Phytochemical Content and Antioxidant Activity of 70% Ethanol and Ethyl Acetate Extracts of Butterfly Pea Flowers - Nabila Naila Amelia; Endang Setyowati; Muhamad Khudzaifi (Lembaga Pengembangan Kinerja Dosen, 2025)
Antioxidants are essential for the body to inhibit or ward off free radicals. Naturally, the body can produce antioxidants, but they can also be obtained from external sources. Interestingly, antioxidants can also be found in plants, one of which is the butterfly pea flower (Clitoria ternatea L.). Compounds contained in butterfly pea flowers, such as flavonoids and phenolics, were macerated with 70% ethanol and ethyl acetate solvents. This study aims to analyze the phytochemical content (flavonoids and phenolics) and evaluate the antioxidant activity of butterfly pea flower extract and their relationship with the PCA (Principal Component Analysis) chemometric method. The total flavonoid content test was carried out with quercetin as a comparator, while the total phenolic content test was carried out with gallic acid as a comparator. Meanwhile, antioxidant activity was carried out using the DPPH method. In this study, the total flavonoid content in the 70% ethanol extract was 4.109 ± 0.027 mg QE/mL, while in the ethyl acetate extract it was 6.616 ± 0.22 mg QE/mL. The total phenolic content produced was 28.276 ± 1.36 mg GAE/mL for the 70% ethanol extract and 31.579 ± 1.59 mg GAE/mL for the ethyl acetate extract, respectively. Meanwhile, the IC50 value for antioxidant activity showed that the ethanol extract had a value of 54.23 ± 2.37 µg/mL, while the ethyl acetate extract had a value of 39.38 ± 3.14 µg/mL. The ethyl acetate extract had higher flavonoid, phenolic, and antioxidant activity than the 70% ethanol extract. Chemometric analysis showed a positive correlation between flavonoids and phenolics in the ethanol solvent. Chemometric analysis showed a relationship between flavonoid and phenolic content in both the ethanol and ethyl acetate solvents and the antioxidant activity of the DPPH method.